Orientación preferencial de frutos y su remoción en Myrtillocactus schenckii (cactaceae) en una zona semiáridad intertropical - Paz Herrera, Leonardo (Universidad Autónoma Metropolitana, 2016)
The equatorial orientation of fruits is present in diverse cacti. In some species from the north hemisphere, have reported they produce bigger fruits and more seeds in southern branches and/or ribs. If these are more attractive for frugivores, we expect them show a preference for them in comparison with those produced in northern branches and ribs. To prove this hypothesis, the case of Myrtillocactus schenckii was studied (preliminary observations suggest a preferential distribution). This study investigated 1) if the cacti shows preferential orientation in fruit production, 2) if consumers shows a preference for southern fruits independently of their availability, and 3) if differences existed in removal between diurnal and nocturnal consumers. To describe the circular distribution, 40 individuals was selected, the cups was divided in two sectors (north and south) with two branches per each sector (those with a clear orientation to its respective sector), where the orientation of each branch was registered, and the different reproductive structures (bud, flower, fruit) were counted. For removal experiments, 20 individual was selected; one branch of each individual was chosen and a determined number of its mature fruits were marked. For three days on 2014, the fruits of 10 individuals were exposed to diurnal frugivores (333 and 251 fruits in April and May, respectively) and 10 individuals for nocturnal (490 and 287, respectively). On April of 2015 the fruits of 5 branches has exposed in the day and another 5 for the night (175 and 156, respectively). For exclusions, bags of tulle netting were used and fruit traps were placed. The fruits present a marked orientation towards the south (µ=185.5°), with 2.2 southern fruits per each northern fruit. The notable lacks of northern fruits didn’t allow evaluation preferences of frugivores. Only 14% of fruits were removed and significant differences between diurnal and nocturnal in 2014 was not detected (p < 0.05), but on 2015, a major removal during the night was occurred. Because the features of their fruits (form, color, position, carbohydrates, and others), M. schenckii is preferably consumed for birds (6 species, highlighting one granivore and two frugivores), however, the nocturnal consumers were the most important removers. The differences between diurnal and nocturnal removal in both years can be caused for differences in the precipitation during the rainy season.; La orientación ecuatorial de frutos se presenta en cactáceas diversas. En algunas especies del hemisferio norte, se ha reportado que los frutos producidos en las ramas y costillas sureñas son más grandes y contienen más semillas. Sí estos son más atractivos para los frugívoros, esperamos que muestren una preferencia por ellos en comparación con los producidos en las ramas y/o costillas norteñas. Para probar esta hipótesis, se estudió el caso de Myrtillocactus schenckii (observaciones preliminares, sugirieron una distribución preferencial). En el presente estudio se investigó 1) si la cactácea muestra orientación preferencial en la producción de frutos, 2) si los consumidores muestran una preferencia por los frutos sureños independientemente de su disponibilidad, y 3) se evaluó sí existen diferencias en la remoción entre consumidores diurnos contra nocturnos. Para describir la distribución circular, se eligieron 40 individuos, en los cuales la copa se dividió en dos sectores (norte y sur), se eligieron 2 ramas por cada sector (las que se encuentren más orientadas a su respectivo sector), en donde se registró la orientación de cada costilla y se contaron las diferentes estructuras reproductivas (yema, flor y fruto). Para los experimentos de remoción, se tomaron 20 individuos; para cada uno se seleccionó una rama donde se marcó un número determinado de frutos maduros. Durante tres días en el 2014, los frutos de 10 individuos fueron expuestos a los frugívoros diurnos (333 y 251 frutos en abril y mayo, respectivamente) y 10 a los nocturnos (490 y 287, respectivamente). En abril del 2015 se expusieron los frutos de 5 individuos durante el día y otros 5 en la noche (175 y 156, respectivamente). Para las exclusiones, se utilizaron bolsas de paño de cielo (tul) y se colocaron trampas para frutos. Los frutos presentaron una marcada orientación hacia el sur (µ=185.5°), con 2.2 frutos sureños por cada norteño. La notable carencia de frutos norteños no permitió evaluar las preferencias de los frugívoros. Sólo se removieron el 14% de los frutos y no se detectaron diferencias significativas entre diurnas y nocturnas para el 2014 (p < 0.05), pero en el 2015 ocurrió una mayor remoción durante la noche. Por las características de sus frutos (forma, color, posición, carbohidratos, y otros), M. schenckii es consumida preferentemente por aves (6 especies, destacando una granívora y dos frugívoras), no obstante, los consumidores nocturnos fueron los removedores más importantes.